Luxembourg : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
This 2012 Article IV Consultation highlights that economic growth in Luxembourg slowed in 2011 amid the euro area sovereign debt crisis. Reflecting sluggish external demand, economic activity is expected to further weaken, with growth projected to decline to 1\2 percent in 2012. Executive Directors have welcomed the continued stability of Luxembourg's economy despite the turbulence in the euro area. They have commended the authorities on measures taken to strengthen the financial sector and to implement recommendations from the Financial Stability Assessment Program update.